Is Endoscopic Dacrocystorhinostomy an Alternative to External Approach Dacrocystorhinostomy - Haider, Shaista; Naqvi, Syed Abid Hassan; Malik, Sidra; Iqbal, Zamir (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the efficacy of Endoscopic Dacrocystorhinostomy with External approach Dacrocystorhino-stomy.Study Design: Comparatives analytical study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, Nov 2017 to  Apr 2018.Methods: This analytical comparative study was carried out at Armed Forces Institute of Ophthalmology Rawalpindi. A total of 80 patients suffering from epiphora due to nasolacrimal duct obstruction were divided into two groups. Group-A underwent endoscopic Dacrocystorhinostomy while Group-B underwent external Dacrocystorhinostomy. At 6-months success of Dacrocystorhinostomy was assessed subjectively from symptomatic relief of epiphora.Results: The efficacy of Group-A treatment was significantly higher as that of Group-B treatment. i.e. Group-A: 90% vs. Group-B: 67.5%. The p-value was calculated to be 0.014 which was statistically significant. Conclusion: Based on this study, it is safe to conclude that endoscopic Dacrocystorhinostomy is an effective alternative to external approach Dacrocystorhinostomy in treating cases with epiphora due to nasolacrimal duct obstruction.